New Rules of the Game: Liability in the Age of Artificial Intelligence - Naumovski, Monika (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
Artificial intelligence (AI) brings many benefits, but also legal challenges, which are also evident in the field of tort liability. The European Union (EU) seeks to balance the promotion of innovation with ensuring effective legal protection for victims through legal regulation. Despite the revision of the Product Liability Directive and the proposed AI Directive, challenges remain in the area of tort liability. Certain consequences of the non-transparency of AI operations, the monopoly on data, and the difficulties in proving damage are difficult to address legally. However, the (proposed) regulation in the EU also contains a number of limitations and unclear requirements that do not contribute to a unified legal framework and legal certainty.